Analytical applications of anthragalol and anthrapurpurine. III.- Spectrophotometric determination of Th (IV) with anthrapurpurine - Capitán, F.; Román, M. (Ars Pharmaceutica (Internet), 1967)
The use of Anthrapurpurin for the spectrophotometric determination of Th (IV), is described. A study is made of the stability of solutions (in ethanol) of Anthrapurpurin Th (IV) complex. The complex obeys Lambert-Beer’s Law, in spite of the fact that the slope of the straight-line is greatly influenced by the concentration of the Anthrapurpurin used. A method is proposed for the determination of Th(IV) for concentrations between 7 and 21 ppm and the error and reproducibility of this method is stablished.